ANALISIS EFEKTIVITAS KEBERLANGSUNGAN MODAL USAHA SIMPAN PINJAM PEREMPUAN PNPM MANDIRI PERDESAAN DI KECAMATAN MENGWI KABUPATEN BADUNG - Verawati, Yenny; Sudirman, Wayan; Marhaeni, A.A I.N (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Implementation of PNPM Rural often do not work well namely, the existence of constraints on its implementation in accordance with the Technical Guidelines for the Operation, disbursement delays, delays in the completion of activities, and others. This study aims to 1) To determine the level of equalization provision of venture capital Women's Savings and Loans (SPP) of PNPM Rural in District Mengwi Badung regency. 2) To determine the effectiveness of the sustainability of the business capital of SPP. 3) To determine the direct effect of the loan amount, number of working hours, priority in running the business, the experience of training and the amount of such assistance to the commitment and effectiveness of sustainability refund venture capital SPP.4) To determine the effect of indirect loan amount, number of hours worked, priority in running the business, training and experience similar to the amount of aid effectiveness venture capital sustainability. This research was conducted in the District Mengwi Badung Regency Bali.Data province used are primary data and secondary data. The sample in this study was 95 head of the group. The analysis technique used is descriptive analysis and inferential statistics using path analysis with multivariate analysis, linearity tests, analysis of the sub-structure equation, the path diagram, Sobel test and interpretation analysis. Research concluded 1) The level of equalization provision of venture capital into the high category. 2) The effectiveness of the sustainability of venture capital into the category of medium 3) The direct effect of the loan amount and a significant negative effect on the commitment of a refund. The number of hours worked and trained experience positive and significant effect on the commitment of a refund. Business priorities and the amount of such assistance is not positive and significant effect on the commitment of a refund. The loan amount but not significant negative effect on the effectiveness of the sustainability of capital. The number of working hours, priority in running the business, training experience, the amount of such assistance, and commitment refund positive and significant impact on the effectiveness of venture capital sustainability. 4) For the indirect effect (indirect effect) in this study indicate that it is real (significant) no mediation effect (intervening) commitment to a refund of the research model is formed.
Keywords: sustainability effectiveness of venture capital, loan amount, hours of work, business priorities, training, and the amount of such assistance, commitment refund